Prefrontal BDNF Levels After Anodal Epidural Direct Current Stimulation in Rats - de Souza Custódio, Juliana C.; Martins, Cleciane W.; Lugon, Marcelo D. M. V.; de Melo Rodrigues, Lívia C.; de Figueiredo, Suely G.; Nakamura-Palacios, Ester M. (Frontiers in Pharmacology, 2018)
This study measured levels of brain-derived neurotrophic factor (BDNF) in the prefrontal cortex (PFC) after single (S) and repetitive (R) anodal epidural DC stimulation (eDCS) over the left medial prefrontal cortex (mPFC). Male Wistar rats received single application of sham (S-sham) or anodal eDCS (S-eDCS) (400 µA for 11 minutes) and had their PFC removed 15, 30 or 60 minutes later. For repetitive brain stimulation, rats received sham (R-sham) or anodal eDCS (R-eDCS) once a day, five consecutive days, and their PFC were removed 24 h after the last application. BDNF isoforms levels were measured by Western blot assays. It was observed that animals receiving S-eDCS showed smaller (p < .01) levels of BDNF 15 minutes after stimulation when compared to S-sham, especially in its mature form (mBDNF p < .001). Levels of BDNF, including mBDNF, were almost like the S-sham at 30 and 60 minutes intervals after stimulation, but not proBDNF, which was significantly smaller (p < .05) than S-sham at these intervals. After five sessions, BDNF levels were higher in the PFC of R-eDCS animals, notably the proBDNF (p < .01) when compared to R-sham. This study showed that levels of BDNF in the PFC, especially the proBDNF, were lower after a single and higher after repetitive anodal eDCS applied over the left mPFC when compared to sham. Therefore, changes of prefrontal BDNF levels may disclose molecular changes underlying the plasticity induced by cortical anodal DC stimulation, which may be opposite if applied in single or multiple sessions.